IMPLEMETASI PENANGANAN DAN PENYELESAIAN KASUS SENGKETA PERTANAHAN DENGAN MEDIASI DI KANTOR PERTANAHAN KABUPATEN MELAWI - NIM. A1011201033, ANES CANDLE LATUMAHINA (Fakultas Hukum Universitas Tanjungpura, 2025)
Abstract The resolution of land dispute cases through mediation is considered one of the best alternative dispute resolution mechanisms compared to other systems and forms of ADR. The problem formulation is